2019
DOI: 10.1021/acs.nanolett.9b02840
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic Field-Free Skyrmion Nucleation at a Nanoengineered Injector Device

Abstract: Magnetic skyrmions are topological solitons that exhibit an increased stability against annihilation [1,2], and can be displaced with low current densities [3], making them a promising candidate as an information carrier [1]. In order to demonstrate a viable skyrmion-based memory device, it is necessary to reliably and reproducibly nucleate, displace, detect, and delete the magnetic skyrmions. While the skyrmion displacement [4-7] and detection [8,9] have both been investigated in detail, much less attention h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
92
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(92 citation statements)
references
References 41 publications
0
92
0
Order By: Relevance
“…2b inset. The applied unipolar pulses during both potentiation and depression were designed and optimized to generate/delete the controlled number of skyrmions using current-induced spin-orbit torques (SOTs) as investigated in our previous study 11 , assisted by current-induced joule heating that contributes to the reduction of skyrmion switching thresholds 28 . In Fig.…”
Section: B Electrical Operation Of Magnetic Skyrmion Artificial Synapsementioning
confidence: 99%
“…2b inset. The applied unipolar pulses during both potentiation and depression were designed and optimized to generate/delete the controlled number of skyrmions using current-induced spin-orbit torques (SOTs) as investigated in our previous study 11 , assisted by current-induced joule heating that contributes to the reduction of skyrmion switching thresholds 28 . In Fig.…”
Section: B Electrical Operation Of Magnetic Skyrmion Artificial Synapsementioning
confidence: 99%
“…One crucial step necessary for realizing a skyrmion‐based device lies in finding a reliable and controllable method of nucleating individual skyrmions. A multitude of nucleation methods have been proposed in recent years and these can be put into three categories based on: electrical currents, [ 10,19–24 ] laser pulses, [ 25–27 ] and locally applied electric fields. [ 28,29 ] Skyrmions can also nucleate at naturally occurring defects in the material; [ 30,31 ] theoretical studies, which consider nonmagnetic defects, find that defects both localize skyrmion nucleation and reduce the nucleation energy barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Since synchrotron-based X-ray microscopes offer continuously tunable excitation photon energy, it has been shown that within a multilayer of several photoresists consecutively stacked at the same spot, each layer can be addressed separately by the resonant photon energy of the respective Following the development of suitable focusing optics for soft X-rays [49][50][51], the first soft X-ray microscopes were installed in the mid-1980s [52,53]. Since then, STXM has developed into a versatile method for characterization of suitably thin specimens from various scientific disciplines, such as biology, medicine, catalysis, material science, magnetism, geology, cosmology, and cultural heritage [54][55][56][57][58][59][60][61][62][63][64]. Figure 1 depicts a scheme of a modern STXM with all basic elements and their respective degrees of freedom [59,65,66].…”
Section: Introductionmentioning
confidence: 99%